2019
DOI: 10.1249/mss.0000000000001904
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow during Exercise in Heart Failure: Effect of Ventricular Assist Devices

Abstract: The results of the study are presented clearly, honestly, and without fabrication, falsification, or inappropriate data manipulation, and statement that results of the present study do not constitute endorsement by ACSM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 32 publications
1
15
1
Order By: Relevance
“…During submaximal exercise (20%-60% V O 2peak ), there is typically a 10%-20% vasodilatory increase in CBF, which is positively correlated with increases in PET CO 2 , MAP, and intra-arterial shear rate (36). We did not observe such increases during exercise in LVAD individuals in our other recent study (37) or in our pretraining LVAD individuals in this study. A novel study by Brassard et al (8) found that, to increase CBF during exercise in untrained LVAD patients with axial-flow pumps, increases in pump speed were required.…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…During submaximal exercise (20%-60% V O 2peak ), there is typically a 10%-20% vasodilatory increase in CBF, which is positively correlated with increases in PET CO 2 , MAP, and intra-arterial shear rate (36). We did not observe such increases during exercise in LVAD individuals in our other recent study (37) or in our pretraining LVAD individuals in this study. A novel study by Brassard et al (8) found that, to increase CBF during exercise in untrained LVAD patients with axial-flow pumps, increases in pump speed were required.…”
Section: Discussioncontrasting
confidence: 56%
“…The improved durability of third-generation LVADs and the continuing scarcity of donor organs has led to an increase in the signifies interaction and post-hoc-revealed differences between pretraining (Pre TR) and post-training (Post TR); P Ͻ 0.001. number of LVAD implantations worldwide for "destination therapy" (1). Although functional capacity improves from preimplantation status, recipients of LVADs still experience impaired aerobic capacity and cerebrovascular function during exercise (7,8,37). Exercise training is an evidence-based adjunct treatment for patients with HF (35,41,42).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations